Homocysteine Metabolism in Pregnancy and Developmental Impacts - D’Souza, Stephen W.; Glazier, Jocelyn D. (Frontiers in Cell and Developmental Biology, 2022)
Homocysteine is a metabolite generated by methionine cycle metabolism, comprising the demethylated derivative of methionine. Homocysteine can be metabolised by the transsulphuration pathway to cystathionine, which requires vitamin B6, or can undergo remethylation to methionine. Homocysteine remethylation to methionine is catalysed by methionine synthase activity which requires vitamin B12, regenerating methionine to allow synthesis of the universal methyl donor S-adenosylmethionine required for methylation and gene transcription regulation. The methyl-group donated for homocysteine remethylation comes from 5-methyltetrahydrofolate generated by the folate cycle, which allows tetrahydrofolate to be returned to the active folate pool for nucleotide biosynthesis. Therefore the integrated actions of the methionine and folate cycles, required to metabolise homocysteine, also perpetuate methylation and nucleotide synthesis, vitally important to support embryonic growth, proliferation and development. Dysregulated activities of these two interdependent metabolic cycles, arising from maternal suboptimal intake of nutrient co-factors such as folate and vitamin B12 or gene polymorphisms resulting in reduced enzymatic activity, leads to inefficient homocysteine metabolic conversion causing elevated concentrations, known as hyperhomocysteinemia. This condition is associated with multiple adverse pregnancy outcomes including neural tube defects (NTDs). Raised homocysteine is damaging to cellular function, binding to proteins thereby impairing their function, with perturbed homocysteine metabolism impacting negatively on embryonic development. This review discusses the ‘cross-talk’ of maternal-fetal homocysteine interrelationships, describes the placental transport of homocysteine, homocysteine impacts on pregnancy outcomes, homocysteine and methylation effects linking to NTD risk and proposes a putative pathway for embryonic provision of folate and vitamin B12, homocysteine-modulating nutrients that ameliorate NTD risk.